1981
DOI: 10.4319/lo.1981.26.4.0635
|View full text |Cite
|
Sign up to set email alerts
|

The effect of environmental factors on phytoplankton growth: Temperature and the interactions of temperature with nutrient limitation1

Abstract: The combined stress of nutrient limitation and suboptimal temperature on growth was studied with turbidostat and chemostat cultures of Scenedesmus sp. and Asterionella formosa. The combined effects were greater than the sum of individual effects and were not multiplicative.In N-and P-limited Scenedesmus sp. and A. formosa the cell quotas (4) of both limiting and nonlimiting nutrients increased with decreasing temperature. At a given temperature cell quotas of limiting nutrients ,also increased with the growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
214
4
6

Year Published

1987
1987
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 335 publications
(236 citation statements)
references
References 24 publications
(24 reference statements)
12
214
4
6
Order By: Relevance
“…Morris et al [25] studied the growth of alga, Phaeodactylum tricornutum, a marine diatom, and reported a considerable increase in protein synthesis rates at night with lower the temperatures, presumably due to the fact that protein synthesis is a significant component of nighttime algal metabolism [82]. Similarly, Rhee and Gotham [83] observed an increase in protein concentration in Scenedesmus sp. with decreasing temperature.…”
Section: Temperaturementioning
confidence: 99%
“…Morris et al [25] studied the growth of alga, Phaeodactylum tricornutum, a marine diatom, and reported a considerable increase in protein synthesis rates at night with lower the temperatures, presumably due to the fact that protein synthesis is a significant component of nighttime algal metabolism [82]. Similarly, Rhee and Gotham [83] observed an increase in protein concentration in Scenedesmus sp. with decreasing temperature.…”
Section: Temperaturementioning
confidence: 99%
“…Although models for the interactions of limiting nutrients with temperature of the temperature effects and light limitations have been proposed (24,25), the actual (very limited) data collected have shown that neither multiplicative nor additive models can explain the interactions of temperature or light with nutrient (N or P) limitation (26,27). Varying two factors simultaneously resulted in larger effects on growth rates then would be predicted by such models.…”
Section: Returning Tomentioning
confidence: 99%
“…This may be explained by the higher metabolic demand and the likelihood of nutrient limitation of cellular processes at higher temperatures (Rhee & Gotham 1981), as colony formation is considered to decrease nutrient uptake by Phaeocystis cells due to the presence of diffusive boundary layers (Ploug et al 1999). Also, the solitary form of Phaeocystis arguably has diverse nutritional strategies (Verity & Medlin 2003).…”
Section: Solitary Vs Colonial Formsmentioning
confidence: 99%